Territorial Impacts of the Ruta Viva Expressway in Peri-Urban Quito (2011–2024): A PCA-Based, Census-Tract Assessment - Pablo Macanchi; Vinicio Moya-Almeida; Paúl Aguilar; Irene Vinueza; Deysi Maisincho; Tatiana Astudillo-Ortega; Francisco Cabrera-Torres (MDPI AG, 2025)
This study examines territorial transformations in five rural parishes of the Metropolitan District of Quito induced by the Ruta Viva expressway (inaugurated in 2013). Using census tracts for 2011, 2017, 2021, and 2024 and four variables—urban land use (COS/BCR), building permits (metropolitan licenses), land value, and population density—we construct a PCA-based territorial impact index and classify outcomes with Jenks natural breaks. Results show marked heterogeneity across parishes: Cumbayá–Tumbaco concentrates high-impact tracts and sustained consolidation, while Pifo–Tababela–Puembo exhibits selective or delayed changes. Over 2011–2024, land value more than tripled on average (with parish-level peaks > 200%), and the population grew 46%, reshaping density patterns. The findings highlight infrastructure-induced reconfiguration and underscore the need to align territorial planning instruments with value capture and inclusionary tools for more equitable and environmentally sustainable outcomes.